Land surface temperature from remote sensing and from an energy water balance model for irrigation management - Corbari C.; Horeschi D.; Ravazzani G.; Mancini M. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
Soil Moisture is recognized as the key variable in the hydrologic water balance for operational purpose as for flash flood forecast system as well as for irrigation management. Respect to this role it is most of the time confined to an internal numerical model variable often without any control with measured data. This is mainly due to its intrinsic space and time variability and to the well known difficulties in assessing its value from remote sensing as from in situ measurements. The present paper investigates the possibility to control surface soil moisture trough the detection of land surface temperature from satellite remote sensing due to the simpler information and availability of infrared satellite images respect to the microwave ones. In this context the paper tries to asses soil moisture values and its spatial and temporal dynamic developing an energy water balance model (FEST-EWB) tested at field scale with fluxes measured from an eddy tower. Modelled soil moisture and temperature values are also compared with operative satellite data (MODIS) and in situ ground measurements.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)